Integrative analysis illustrates the role of PCDH7 in lung cancer development, cisplatin resistance, and immunotherapy resistance: an underlying target - Li, Huakang; Xu, Haoran; Guo, Hong; Du, Kangming; Chen, Diang (Frontiers in Pharmacology, 2023)
Background: Cisplatin resistance is a common clinical problem in lung cancer.However, the underlying mechanisms have not yet been fully elucidated, highlighting the importance of searching for biological targets Methods: Bioinformatics analysis is completed through downloaded public data (GSE21656, GSE108214 and TCGA) and specific R packages. The evaluation of cell proliferation ability is completed through CCK8 assay, colony formation and EdU assay. The evaluation of cell invasion and migration ability is completed through transwell and wound-healing assay. In addition, we evaluated cell cisplatin sensitivity by calculating IC50.Results: Here, we found that PCDH7 may be involved in cisplatin resistance in lung cancer through public database analysis (GSE21656 and GSE108214).Then, a series of in vitro experiments was performed, which verified the cancerpromoting role of PCDH7 in NSCLC. Moreover, results of IC50 detection showed that PCDH7 might be associated with cisplatin resistance of NSCLC.Next, we investigated the single-cell pattern, biological function and immune analysis of PCDH7. Importantly, we noticed PCDH7 may regulate epithelialmesenchymal transition activity, as well as the local infiltration of CD8+ T and activated NK cells. Furthermore, we noticed that patients with high PCDH7 expression might be more sensitive to bortezomib, docetaxel and gemcitabine, and resistant to immunotherapy. Finally, a prognosis model based on three PCDH7-derived genes (GPX8, BCAR3 and TNS4) was constructed through a machine learning algorithm, which has a good prediction ability on NSCLC patients survival.Our research has improved the regulatory framework for cisplatin resistance in NSCLC and can provide direction for subsequent related research, especially PCDH7.